Does mild hyperglycemia in 75gm Glucose Tolerance Test (GTT) affect outcome in pregnant women? - J., Karthiga Prabhu; M., Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Glucose tolerance in pregnancy is fundamentally linked to fetal growth. The relationship between maternal glycemia and adverse outcomes is a continuous process, with no distinct cut off point for increased risk. The objective of the study is to find out whether mild hyperglycemia in 2 hour 75 gm Glucose Tolerance Test (GTT) affects maternal and perinatal outcome in pregnant women. Methods: This case control study was conducted in SRM Medical College during a 10-month period. Mild hyperglycemia was diagnosed when the - 2hour non- fasting 75gm GTT was between 120-139 mg/dl and Controls were women with 2hour nonfasting 75gm GTT <120mg/dl. Maternal and neonatal parameters were noted and the results were compared. Results: During the study period 142 delivered women had mild hyperglycemia, of which 10 patients on subsequent blood sugar monitoring required insulin for blood sugar control. There was significant family history of diabetes in women with mild hyperglycemia when compared to controls. There was no significant difference in incidence of hypertension, hypothyroidism, preterm delivery and caesarean section between the two groups. LGA (Large for gestational age babies) (p=0.001) and serum triglyceride levels (p=0.04) were significantly more in women with mild hyperglycemia when compared to controls. Conclusions: Mild hyperglycemia during pregnancy should not be ignored and periodic blood sugar monitoring should be done to improve maternal and fetal outcome.